2002
DOI: 10.1074/jbc.m206700200
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Decay Is Rapidly Induced after Spore Germination ofSaccharomyces cerevisiae

Abstract: Spores from the yeast Saccharomyces cerevisiae can germinate and resume their vegetative growth when placed in favorable conditions. Biochemical studies on germination have been limited by the difficulty of obtaining a pure population of spores germinating synchronously. Here, we report that spores can be purified and sorted according to their size by centrifugal elutriation and that these spores are able to germinate synchronously. Synchronizing their development has allowed reevaluating certain parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 50 publications
(47 reference statements)
2
41
0
1
Order By: Relevance
“…The ability of fungal spores to store prepackaged mRNA has been reported in S. cerevisae, A. nidulans and N. crassa [19,20]. The prestored mRNA in conidia can be activated and translated rapidly in the presence of nutrients and soon after germination the stored mRNA decayed [21]. In a previous study, we found stored mRNA in T. rubrum conidia and this had similar expression characteristics to the mRNA of the Cluster I genes in this study [13].…”
Section: Discussionsupporting
confidence: 82%
“…The ability of fungal spores to store prepackaged mRNA has been reported in S. cerevisae, A. nidulans and N. crassa [19,20]. The prestored mRNA in conidia can be activated and translated rapidly in the presence of nutrients and soon after germination the stored mRNA decayed [21]. In a previous study, we found stored mRNA in T. rubrum conidia and this had similar expression characteristics to the mRNA of the Cluster I genes in this study [13].…”
Section: Discussionsupporting
confidence: 82%
“…These stored mRNA are primed for rapid activation and translation in the presence of nutrients. The decay of spores containing mRNA is induced soon after germination [34]. In this study, mRNA of genes in cluster I existed in spores before induction of germination and the expression levels of those genes were down-regulated immediately at the onset of germination.…”
Section: Discussionmentioning
confidence: 74%
“…The first descriptions of spore quiescence were obtained using strain backgrounds that exhibit moderately reduced sporulation efficiency and kinetics (Brengues et al, 2002; Hopper et al, 1974). To confirm that SK1 spores attain metabolic quiescence, we measured dissolved O 2 consumption rates of sporulating cells and found that terminally differentiated spores (36 hr post-induction) consume oxygen at ~4% the rate of cells at time 0 of time courses, demonstrating that mitochondrial respiration is dramatically downregulated during sporulation (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Our microarray data presented in Figure 1D measured RNA produced from both DNA strands across the entire genome at high resolution. Although this data measured RNA from terminally sporulated cells at the 20 hr time point, as mRNA stability is dramatically upregulated during sporulation (Brengues et al, 2002), it nevertheless afforded us a means to evaluate this hypothesis. When we reassembled this data to construct a globally averaged protein coding gene transcript profile, we found, as expected, that the abundance of transcripts from this averaged transcript unit was reduced in jhd2Δ mutants, (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation